Alan Gilbert y Ward M. Peter. Housing, the state and the poor : policy and practice in three Latin American Cities. Londres ; Nueva York ; New Rochelle ; Melbourne ; Sidney : Cambridge University Press, 1985. 320 p. - Schteingart, Martha (Estudios Demográficos y Urbanos, 1986)
ALAN GILBERTY WARD M. PETER. Housing, the State and the Poor: Policy and Practice in three Latin American Cities. Cambridge University Press, Latin American Studies, Londres, Nueva York, New Rochelle, Melbourne, Sidney, 1985.